Champion eaudiobook - Lu, Marie (Legend, 2013)
June and Day have sacrificed so much for the people of the Republic and now their country is on the brink of a new existence. June is back in the good graces of the Republic, working within the government's elite circles as Princeps Elect while Day has been assigned a high level military position. Just when a peace treaty is imminent, a plague outbreak causes panic in the Colonies, and war threatens the Republic's border cities. This new strain of plague is deadlier than ever, and June is the only one who knows the key to her country's defense. But saving the lives of thousands will mean asking the one she loves to give up everything he has.